Coercion and Social Welfare in Public Finance : Economic and Political Perspectives - Martinez-Vazquez, Jorge; Winer, Stanley L. (Cambridge : Cambridge University Press, 2014)
Although coercion is a fundamental and unavoidable part of our social lives, economists have not offered an integrated analysis of its role in the public economy. The essays in this book focus on coercion arising from the operation of the fiscal system, a major part of the public sector. Collective choices on fiscal matters emerge from and have all the essential characteristics of social interaction, including the necessity to force unwanted actions on some citizens. This was recognized in an older tradition in public finance which can still serve as a starting point for modern work. The contributors to the volume recognize this tradition, but add to it by using contemporary frameworks to study a set of related issues concerning fiscal coercion and economic welfare. These issues range from the compatibility of an open access society with the original Wicksellian vision to the productivity of coercion in experimental games.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).
Keywords: Finance, Public; Public welfare; State, The; Social policy